Tows Matrix Business Strategy Analysis of PT XYZ - Angga Rullian; Lisna Mahera; Sonya Agustin; Syaeful Y Surawijaya; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2025)
. In the increasingly complex landscape of business energy and infrastructure, corporate strategy is a determinant of corporate desires. PT PGAS Solution, as a subsidiary of PGN Group (Holding Migas Pertamina), has a strategic position in providing engineering, procurement, construction (EPC), and operation and maintenance (O&M) services. Through a sharing session entitled "Governance of Corporate Strategy Management Analysis", the company explained the implementation of SWOT which was developed into TOWS Matrix as a strategy formulation approach. This study analyzes the SO, WO, ST, and WT strategy structures compiled by PGAS Solution, and brings out their relevance to the challenges of the oil and gas industry and opportunities for synergy between BUMN. The results of the analysis show that the company adopts a proactive strategy approach based on collaboration, efficiency, and strengthening internal capabilities, especially in the management of downstream and midstream oil and gas projects.